Responses of superficial and deep blood Vessels to cooling - G. Mitchell; J. Enslin; M. Mastrolonardo; B. Shunn; A. Stewart (AOSIS, 1982)
Dilation of blood vessels seems desirable from a therapeutic point of view. Results suggest that application of icepacks may not be the ideal technique to use, as icepacks, although lowering skin temperature to levels at which skin vessels will dilate, will not lower muscle temperatures to levels at which deep vessel constriction is inhibited. Results further show that to achieve dilation of vessels, it is not necessary to apply icepacks for longer than 8-10 minutes.